UTILIZATION OF ZEOLITS FOR WATER FILING - Dur, Sajaratud (UIN Sumatera Utara, 2018)
This study aims to obtain zeolite powder from Sarulla natural zeolite as an adsorbent, particle size of zeolite powder, and water analysis before and after water purification. The benefit is to increase the benefits of zeolite to a higher economic value.The method used is the grinding mill method to smooth the zeolite chunks. Whereas the water purification process uses a screening process.The results of this study were zeolite produced at 200 mesh or 74 microns, and the purification was successfully carried out.The conclusion of this study is that zeolite powder obtained from Sarulla natural zeolite as an adsorbent, obtained zeolite particles namely 200 mesh or 74 microns, and the water purification process was successfully carried out.